Dermocosmetics in the management of Acne Vulgaris - Anna Mich; Radosław Ciesielski; Klaudia Perkowska; Anna Kaźmierczak; Wiktoria Izdebska; Patrycja Sornek; Agata Borkowska; Anna Kiełb; Igor Pawlak; Jakub Stanek (Nicolaus Copernicus University in Toruń, 2024)
Treating acne vulgaris remains a significant challenge for dermatologists. Dermocosmetics are becoming an essential component of acne management. The active ingredients in dermocosmetics help support dermatological treatments, while gentle formulations help maintain the skin's lipid barrier, reduce transepidermal water loss, and minimize the risk of irritation. Our objective was to review the active ingredients and various preparations used in dermocosmetics for acne, and to emphasize the clinical evidence supporting their effectiveness.